FCGR2/3 polymorphisms are associated with susceptibility to Kawasaki disease but do not predict intravenous immunoglobulin resistance and coronary artery aneurysms - Uittenbogaard, Paula; Netea, Stejara A.; Tanck, Michael W. T.; Geissler, Judy; Buda, Piotr; Kowalczyk-Domagała, Monika; Okarska-Napierała, Magdalena; van Stijn, Diana; Tacke, Carline E.; , US Kawasaki Disease Genetics Consortium; Burgner, David P.; Shimizu, Chisato; et al. (Frontiers in Immunology, 2024)
Introduction: Kawasaki disease (KD) is a pediatric vasculitis that can result in coronary artery aneurysm (CAA) formation, a dangerous complication. Treatment with intravenous immunoglobulin (IVIg) significantly decreases CAA risk, possibly through competitive binding to Fc-gamma Receptors (Fc𝛾Rs), reducing the binding of pathological immune complexes. However, ~20% of children have recrudescence of fever and have an increased CAA risk. Therefore, we aimed to identify genetic markers at the FCGR2/3 locus associated with susceptibility to KD, IVIg resistance or CAAs. Methods: We investigated the association of single nucleotide polymorphisms (SNPs) and copy number variations (CNVs) at the FCGR2/3 locus with KD susceptibility, IVIg resistance and CAA risk using a family-based test (KD susceptibility) and case-control analyses (IVIg resistance, CAA risk) in different cohorts adding up to 1,167 KD cases in total. We performed a meta-analysis on IVIg resistance and CAA risk including all cohorts supplemented by previous studies identified through a systematic search. Results: FCGR2A-p.166His was confirmed to be strongly associated with KD susceptibility (Z=3.17, P=0.0015). In case-control analyses, all of the investigated genetic variations at the FCGR2/3 locus were generally not associated with IVIg resistance nor with CAA risk, apart from a possible association in a Polish cohort for the FCGR3B-NA2 haplotype (OR 2.15 [95% CI 1.15-4.01], P=0.02). Meta-analyses of all available cohorts revealed no significant associations of the FCGR2/3 locus with IVIg resistance or CAA risk. Discussion: FCGR2/3 polymorphisms are associated with susceptibility to KD, but not with IVIg resistance and CAA formation. Currently known genetic variations at the FCGR2/3 locus are not useful in prediction models for IVIg resistance or CAA risk.